Mitigation‐driven translocations: are we moving wildlife in the right direction?. Issue 2 (16th January 2015) - Germano, Jennifer M; Field, Kimberleigh J; Griffiths, Richard A; Clulow, Simon; Foster, Jim; Harding, Gemma; Swaisgood, Ronald R
Abstract : Despite rapid growth in the field of reintroduction biology, results from scientific research are often not applied to translocations initiated when human land‐use change conflicts with the continued persistence of a species' population at a particular site. Such mitigation‐driven translocations outnumber and receive more funding than science‐based conservation translocations, yet the conservation benefit of the former is unclear. Because mitigation releases are economically motivated, outcomes may be less successful than those of releases designed to serve the biological needs of species. Translocation as a regulatory tool may be ill‐suited for biologically mitigating environmental damage caused by development. Evidence suggests that many mitigation‐driven translocations fail, although the application of scientific principles and best practices would probably improve the success rate. Lack of transparency and failure to document outcomes also hinder efforts to understand the scope of the problem. If mitigation‐driven translocations are to continue as part of the growing billion‐dollar ecological consulting industry, it is imperative that the scale and effects of these releases be reported and evaluated.